Penerapan Sistem Antrian Sebagai Upaya Mengoptimalkan Pelayanan Pembayaran Pajak Kendaraan Bermotor Di Kantor Samsat Kota Palu - Serlyng; Jaya, A I; Sahari, A (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTOne phenomenon that often occurs in daily life is a queue phenomenon. When queue is too long, it will harm the customer, therefore improving system servicing and optimizing the number of servers expected to reduce the queue, so the process of waiting does not happen too long. In the process of payment of motor vehicle tax at SAMSAT Palu City, it has been known that the queuing system using model Multi Channel- Multi Phase. Thissystem occurs if there are two or more facilities serving with services more than one phase. The ains of thisreseareh are to determine the characteristics of quene system and to know the number of person that required in the process of rehiele tax payment so that the service becomes optimal. The results stated that each phases of 1,2,3 and 4 is consist of 2 person, and motor vehicle tax payment servises in SAMSAT Palu is 108,9 minutes forone customer. Once optimized, an alternative solution to queue problem in SAMSAT Palu city is added person.The addition of 3 person at phase 1, 4 person phase 2, 5 person at phase 3 and phase 4. Will shorten the queuelength from (108,9) minutes to (29,76) minutes for one customer.Keywords : Model Multi Channel- Multi Phase, Samsat Queue.